Post-transcriptional gene silencing of glucanase inhibitor protein in Phytophthora cinnamomi - Ferreira, Patrick (2023)
Ink disease is considered one of the most significant causes contributing to the decline of chestnut orchards. The reduced yield of Castanea sativa Mill can be attributed to two main species: Phytophthora cinnamomi and Phytophthora cambivora, with the first being the main pathogen responsible for ink disease in Portugal. P. cinnamomi is a highly aggressive and widely distributed plant pathogen, capable of infecting nearly 1000 host species. This oomycete causes substantial economic losses and is accountable for the decline of numerous plant species in Europe and worldwide. To date, no effective treatments are available to combat these pathogens. Given chestnut’s economic and ecological significance, particularly in Portugal, it is crucial to investigate the molecular mechanisms underlying the interaction between Phytophthora species and host plants. This can be achieved through the study of the glucanase inhibitor protein (GIP) produced by P. cinnamomi during infection. The technique of RNA interference (RNAi) was employed to suppress the GIP gene of P. cinnamomi. The resulting transformants, carrying the silenced gene, were used to infect C. sativa, allowing for the assessment of the effects of gene silencing on the plant’s phenotype. Additionally, bioinformatics tools predicted the secretion of GIP protein. The obtained results validate RNAi as a potential alternative tool for studying molecular factors and for controlling and managing P. cinnamomi.